Primary School Teachers’ Continuing Professional Development (CPD) : Teachers’ Reflection of Expectation and Reality - Okky Leo Agusta; Muhammad Kristiawan (Universitas Pahlawan Tuanku Tambusai, 2021)
Teachers’ quality plays a paramount role in the improvement of quality of education. This paper describes the reflection of expectation and reality from the concept and the implementation of CPD of Primary School teacher in Indonesia. The objectives of CPD are increasing teachers’ professional development, increasing education services and upgrading professional qualification. In Indonesia, the objectives CPD only touches increasing education services and professional development. Teachers should involve in CPD activities, they are in self-development, scientific publication and innovative works. The reality from the implementation of CPD, Indonesia’s Education Development Index (EDI) is still on average level. It shows CPD activities have not brought education service improvement in longlife learning. In term of professional development, there are many teachers who are not pass credit score to have higher fungtional position and the main factors are less of motivation and commitment of teachers. In the other line, teachers who have pursued master qualification commonly have been pass credit score.